A retrospective regional audit of Cytomegalovirus (CMV) laboratory diagnostics in Crohn's/Colitis patients in Northern Ireland – 'towards a diagnostic algorithm'. Issue Volume 1(2019)Issue A (8th March 2019) - Feeney, Susan; Turner, Graham; Murphy, Seamus; Tham, Tony; Jacob, George; Morrison, Graham; Watson, Peter; Kelly, Paul; Patterson, Lynsey; Coyle, Peter V
Abstract : Introduction: Concurrent cytomegalovirus (CMV) in inflammatory bowel disease (IBD) related colitis, (Ulcerative Colitis (UC) or Crohn's Disease (CD) is an important yet complex scenario associated with high rates of colectomy and other morbidity. This regional audit aimed to identify baseline standards for a virological diagnostic-based approach for the identification of those at risk of CMV reactivation (flare) in the setting of IBD. Methods: Retrospective, cross-sectional study over a three year time-period, January 2010–March 2013, involving all five Northern Ireland HSC Trusts. Sample cohort n =277 IBD patients of which n =106 further grouped as SRC 'severe acute colitis and/or steroid refractory colitis'. Seven audit standards were assessed including specimen(s) submission for CMV diagnostic analysis, antiviral therapy, ascertainment of colectomy rate, and result communication protocol. Findings: Audit primarily found a need to better define test requesting protocols (optimal sample required for optimal serology and molecular diagnostics), and a need to work towards timeliness in both test requesting and result reporting. This audit also identified the high risk patient group (SRC) when test positive for CMV (PCR and/or histopathology) three times more likely to undergo colectomy (OR 3.16, 95 % CI (0.74, 13.21; P =0.06). Conclusions: Diagnostic-based patient identification is optimal to identify those most at risk of CMV reactivation in the IBD setting. The serological IgG profile is key in risk assessment of potential reactivation, together with quantitative CMV PCR in colonic tissue, with/without supportive histopathology, as the most sensitive and timely means of identify those high risk patients.